A Methanogenic Consortium Was Active and Exhibited Long-Term Survival in an Extremely Acidified Thermophilic Bioreactor - Han, Wenhao; He, Pinjing; Lin, Yucheng; Shao, Liming; Lü, Fan (Frontiers in Microbiology, 2019)
Acid crisis characterized by acid accumulation and/or low pH is a common reason for the failure of anaerobic digestion, which is usually applied for wastewater and waste treatment. Acid-tolerant methanogens are rarely reported to be active in the artificial anaerobic digester. In this study, we observed that the thermophilic methanogenesis by a consortium in the form of flocs and not granules could still be recovered during long-term operation at acetate concentration of up to 104 mM and pH 5.5 by adjusting the pH gradually or directly to pH 5.5 or 5.0. The acclimation process involving the gradual decrease in pH could enhance the resistance of the consortium against extreme acidification. The stable isotopic signature analysis of biogas revealed that Methanosarcina, which produced methane through acetoclastic methanogenesis pathway, was the predominant methane producer when the pH was decreased gradually to 5.0. Meanwhile, the abundance of Coprothermobacter increased with a decrease in pH. Contrastingly, when directly subjected to an environment of pH 5.5 and 104 mM acetate (15.84-mM free acetic acid) after a 42-day lag phase, Methanothermobacter was the predominant methanogen. Methanothermobacter initiated methane production through the hydrogenotrophic pathway and formed syntrophic relationship/consortium with the potential acetate-oxidizing bacteria, Thermacetogenium and Coprothermobacter. Comparative metagenomic and metatranscriptomic analysis on this self-adapted and acid-tolerant consortium revealed that the genes, such as GroEL, DnaK, CheY, and flagellum-related genes (FlaA, FlgE, and FliC) from Anaerobaculum, Thermacetogenium, and Coprothermobacter were highly overexpressed in response to system acidification. Microbial self-adaptation patterns (community structure adjustment, methanogenesis pathway shift, and transcriptional regulation) of thermophilic methanogenic consortium to gradual and sudden acidification were evaluated by integrated stable isotopic signature and comparative meta-omic approaches. The study elucidated the acid-resistant mechanism of thermophilic methanogenic consortium and deepened our knowledge of the function, interaction, and microbial characteristics of Methanosarcina, Methanothermobacter, and Coprothermobacter under extreme acidic environment.